ROLE OF CUCURBITACEOUS ROOTSTOCKS ON VEGETATIVE GROWTH, FRUIT YIELD AND QUALITY OF BITTER GOURD (MOMORDICA CHARANTIA L.) S CIONS THROUGH GRAFTING - N. A. Tamilselvi; L. Pugalendhi (Journal of Animal and Plant Sciences, 2018)
The aim of this study was to determine whether grafting could improve plant growth, yield and quality of bitter gourd through monitoring the changes induced by different rootstocksscion combinations. Side grafting technique was followed in this experiment. The grafted and non-grafted plants were grown under pandal system. Among the 12 graft combinations, Palee F scion grafted onto pumpkin (Cucurbita moschata Duch.ex Poir) rootstock recorded highest 1 values for vegetative and flowering characters viz., vine length at final harvest ( 856.6 cm), number of primary branches (13.1), days to first female flower appearance ( 68.3 days), node number to first female flower appearance (25.4) and sex ratio (17.2). The highest values for fruit yield (3.5 kg /per vine), fruit number ( 27.8) and weight (183.6 g) were also observed in Palee F scion grafted onto pumpkin ( C. moschata Duch.ex Poir) rootstock without changes in fruit quality 1 parameters viz., ascorbic acid and total soluble solids content. Larger leaf area and total dry matter content of the aforementioned graft combination contributed mainly for highest vine length, fruit yield and higher total chlorophyll content. From this study, pumpkin (C. moschata Duch.ex Poir) followed by sponge gourd (Luffa cylindrica L.) rootstock could be identified as best rootstocks for grafting with bitter gourd scions due to characteristics like graft affinity, compatibility and vigorous root system which help to increase growth, yield and productivity without any quality defeat. Although alternative pesticides and other physical
Keywords: Grafting; Bitter gourd; Cucurbitaceous rootstocks; Growth; Yield; Quality.